Social and Economic Costs of Attention-Deficit/Hyperactivity Disorder Across the Lifespan. Issue 1 (January 2022) - Sciberras, Emma; Streatfeild, Jared; Ceccato, Tristan; Pezzullo, Lynne; Scott, James G.; Middeldorp, Christel M.; Hutchins, Paul; Paterson, Roger; Bellgrove, Mark A.; Coghill, David
Objective: To determine the financial and non-financial costs of Attention-Deficit/Hyperactivity Disorder (ADHD) across the lifespan. Method: The population costs of ADHD in Australia were estimated for the financial year 2018 to 2019 using a prevalence approach to cost estimation across all ages. Financial (healthcare, productivity, education and justice systems, and deadweight losses) and non-financial costs were measured (Disability Adjusted Life Years (DALYs)). Results: The total social and economic cost of ADHD in 2018 to 2019 were US$12.76 billion (range US$8.40 billion to US$17.44 billion, with per person costs of US$15, 664 per year). Productivity costs made up 81% of the total financial costs, followed by deadweight losses (11%), and health system costs (4%). Loss in terms of wellbeing was significant (US$5.31 billion). Conclusion: There is a need to raise public awareness of the considerable socioeconomic impact and burden of ADHD in order to drive investment and policy decisions that improve identification and treatment of ADHD.